PERENCANAAN KEUANGAN HALAL SEJAK DINI: PENDEKATAN SYARIAH YANG CERDAS - Nurzansyah, Muhammad; Samsuri; Maudi Aprilla Putri; Dini Anggraini (Jurnal Istimā, 2025)
This program aims to increase the awareness and understanding of the younger generation about the importance of Islamic financial planning from an early age as an effort to avoid financial risks in the future and optimize asset management according to Islamic principles. The activity was carried out through a workshop at the Ustman Bin Affan Cipayung Islamic Boarding School, East Jakarta, on April 20, 2025, with a total of 80 participants. The methods used include interactive seminars, simulations, and exercises in preparing sharia-based personal financial plans. The results of the activity showed that 70 out of 80 participants were able to prepare Islamic financial planning properly and understand the basic principles of halal financial management. These findings confirm that Islamic financial literacy education is effective in improving the financial competence of the younger generation and encouraging the application of Islamic economic principles in daily life.